NILAI-NILAI MULTIKULTURAL DALAM ISLAM MELAYU PADA KEHIDUPAN BERMASYARAKAT - Achmad Fadil; Dwi Yusanti; Moh Restu Hoeruman; Rika Hasmayanti; Imam Tauhid (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
Malay Islam represents a prominent pattern of Islamic civilization that developed in the Malay World, encompassing Indonesia, Malaysia, Brunei Darussalam, Singapore, and Southern Thailand. The evolution of Malay Islam took place within a pluralistic social environment, giving rise to multicultural values and tolerant attitudes that define its unique civilizational character. This study aims to analyze multicultural values in Malay Islam and examine the tolerant behaviors of Malay Muslim society in social life. The study employed a qualitative approach using a literature review method analyzing 30 relevant secondary data documents. Data were gathered from indexed scientific articles, academic books, and relevant research findings focusing on Malay Islam, multiculturalism, and tolerance. Data analysis was conducted using content analysis techniques consisting of identification, classification, interpretation, and data synthesis. The findings indicate that multicultural values in Malay Islam are rooted in the principles of unity in diversity, manners and character (adab and budi), and deliberation and consensus (musyawarah and muafakat) derived from Islamic teachings and Malay philosophy. Meanwhile, the tolerance of Malay Muslim society is expressed through empathy, openness to plurality, mutual assistance, and social solidarity. These results demonstrate that Malay Islam builds social harmony by integrating Islamic values and Malay culture, rendering diversity a strength in forging unity and a peaceful community life. ABSTRAK Islam Melayu merupakan salah satu corak peradaban Islam yang berkembang di kawasan Alam Melayu, meliputi Indonesia, Malaysia, Brunei Darussalam, Singapura, dan Thailand Selatan. Perkembangan Islam Melayu berlangsung dalam lingkungan masyarakat yang majemuk sehingga melahirkan nilai-nilai multikultural dan sikap toleransi yang menjadi karakter khas peradabannya. Penelitian ini bertujuan untuk menganalisis nilai-nilai multikultural dalam Islam Melayu serta mengkaji sikap toleransi masyarakat Islam Melayu dalam kehidupan sosial. Penelitian menggunakan pendekatan kualitatif dengan metode literature review terhadap 30 dokumen data sekunder yang relevan. Data diperoleh dari berbagai artikel ilmiah terindeks, buku akademik, dan hasil penelitian yang relevan mengenai Islam Melayu, multikulturalisme, dan toleransi. Analisis data dilakukan melalui teknik content analysis dengan tahapan identifikasi, klasifikasi, interpretasi, dan sintesis data. Hasil penelitian menunjukkan bahwa nilai-nilai multikultural dalam Islam Melayu berlandaskan pada prinsip kesatuan dalam keberagaman, adab dan budi, serta musyawarah dan muafakat yang bersumber dari ajaran Islam dan falsafah Melayu. Sementara itu, toleransi masyarakat Islam Melayu diwujudkan melalui sikap tenggang rasa, keterbukaan terhadap kemajemukan, gotong royong, dan solidaritas sosial. Temuan ini menunjukkan bahwa Islam Melayu membangun harmoni sosial melalui integrasi nilai keislaman dan budaya Melayu sehingga keberagaman menjadi kekuatan dalam membentuk persatuan dan kehidupan masyarakat yang damai.